FUNGSI DAN MAKNA YAHARI/YAPPARI DALAM NOVEL RYUSEI NO KIZUNA KARYA KEIGO HIGASHINO (SUATU TINJAUAN DESKRIPTIF) - Kade Raga Adiputri, Ida Ayu (Humanis, 2015)
This research analyzed the function and meaning of yahari/yappari and sasuga as adverbs in Japanese Language. The data source was taken from a novel by Keigo Higashino entitled “Ryusei no Kizuna”. The method of this research was qualitative descriptive method. The result of the research showed that yahari/yappari has three functions and sasuga has one function. Yahari/yappari has three meanings and sasuga has two meanings. Yahari/yappari can be replaced by sasuga when it showed the situation conforms to the speaker’s expectation with a strong feeling. Then sasuga can be replaced by yahari/yappari when it showed that the speaker was impressed by the situation conforms to his/her expectation.
Keywords: function, meaning, yahari/yappari, sasuga